A theory of existential psychology - Lambley, Peter (Department of Psychology, 2016)
The theory presented in this dissertation is intended as a contribution to a central problem faced by contemporary psychologists, namely the problem of the role of value in the study of human action. This problem can be phrased in the following fashion: most contemporary writers in the philosophy of science agree that some a priori framework is essential for the study of naturally-occurring phenomena (Feyerabend, 1965; Katsoff, 1953; Turner, 1967). Such a framework serves the dual function of indicating, in a paradigmatic fashion (Kuhn, 1962, 1970), the direction research should take and provides an underlying epistemology and methodology enabling relevant findings to be interpreted.